Dynamic changes in microRNA expression profiles reflect progression of Barrett's esophagus to esophageal adenocarcinoma - Slaby, Ondrej; Srovnal, Josef; Radova, Lenka; Gregar, Jan; Juracek, Jaroslav; Luzna, Pavla; Svoboda, Marek; Hajduch, Marian; Ehrmann, Jiri (Carcinogenesis, 2015)
Esophageal adenocarcinoma (EAC) is highly aggressive malignancy that frequently develops from Barrett's esophagus (BE), a premalignant pathologic change occurring in the lower end of the esophagus. MicroRNAs (miRNAs) are small, non-coding RNAs that function as posttranscriptional regulators of gene expression and were repeatedly proved to play key roles in pathogenesis of BE as well as EAC. In our study, we used Affymetrix GeneChip miRNA arrays to obtain miRNA expression profiles in total of 119 tissue samples [24 normal esophageal mucosa (EM), 60 BE and 35 EAC]. We identified a number of miRNAs, that showed altered expression progressively in sequence EM, BE and EAC, including for instance miR-21, miR-25, miR-194 and miR-196a with increasing levels (P < 0.0015) and miR-203, miR-205, miR-210 and miR-378 with decreasing levels (P < 0.0001). The subsequent analysis revealed four diagnostic miRNA signatures enabling to distinguish EM and BE [12 miRNAs, area under curve (AUC) = 0.971], EM and EAC (13 miRNAs, AUC = 1.0), BE without and BE with dysplasia (21 miRNAs, AUC = 0.856) and BE without dysplastic changes and BE with dysplasia together with EAC (2 miRNAs, AUC = 0.886). We suggest that miRNA expression profiling expands current knowledge in molecular pathology of Barrett's-based carcinogenesis and enables identification of molecular biomarkers for early detection of BE dysplasia and progression to EAC.
Keywords: regulace genové exprese u nádorů; Oligonucleotide Array Sequence Analysis; nádorové biomarkery; Prognosis; mikro RNA; studie případů a kontrol; Biomarkers, Tumor; retrospektivní studie; Humans; staging nádorů; následné studie; lidé středního věku; Neoplasm Staging; Middle Aged; Barrettův syndrom; prognóza; Follow-Up Studies; mužské pohlaví; nádory jícnu; Adenocarcinoma; ROC Curve; Barrett Esophagus; Disease Progression; Gene Expression Regulation, Neoplastic; Esophageal Neoplasms; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; lymfatické metastázy; Lymphatic Metastasis; ženské pohlaví; ROC křivka; stanovení celkové genové exprese; MicroRNAs; lidé; Case-Control Studies; Gene Expression Profiling; ezofágus; Aged; senioři; progrese nemoci; Esophagus; Male; Retrospective Studies; adenokarcinom; Female